THE ROLE OF THE TEACHER AND EIGHT KEY COMPETENCE FOR LIFELONG LEARNING. CASE STUDY POLISH SCHOOL IN REZEKNE - Szulc, Sylwia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
In this article author present the impact of teacher competences on the role played in school. The object of the research is the role played by the teacher in the State Polish Grammar School in Rezekne. In order to compare theory with practice, empirical studies have been conducted in the two - month practice in State Polish Grammar School in Rezekne, which were completed within the practice of Erasmus+.